2019
DOI: 10.1021/acsomega.9b02241
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling the Dependence between Hydroxyl Radical Generation and Performance of Fenton Systems with Complexed Iron

Abstract: Humiclike substances (HLS) have been demonstrated to be useful auxiliaries to drive the (photo)-Fenton process at mild pH, by avoiding iron inactivation via formation of active complexes. However, the actual performance of the process is affected by a manifold of opposite processes. In this work, the generation of hydroxyl radical-like reactive species in the Fentonlike process has been investigated using electron paramagnetic resonance, employing 5,5-dimethyl-1-pyrroline-N-oxide as a probe molecule. The signa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 34 publications
1
4
0
Order By: Relevance
“…The photocatalytic generation of • OH species to confirm the radical oxidation of the SARS-CoV-2 was checked by ESR analysis under similar solar light with UV light cut-off (400 nm) using DMPO as a trapping agent: the relevant spectra are reported in Figure 3. Unlike bare TiO 2 , the pattern of the typical signals of DMPO-• OH adduct [51] was notably detected in Ag@TiO 2 , confirming the high photonic synergism obtained in Ag-TiO 2 .…”
Section: Antiviral Resultssupporting
confidence: 59%
“…The photocatalytic generation of • OH species to confirm the radical oxidation of the SARS-CoV-2 was checked by ESR analysis under similar solar light with UV light cut-off (400 nm) using DMPO as a trapping agent: the relevant spectra are reported in Figure 3. Unlike bare TiO 2 , the pattern of the typical signals of DMPO-• OH adduct [51] was notably detected in Ag@TiO 2 , confirming the high photonic synergism obtained in Ag-TiO 2 .…”
Section: Antiviral Resultssupporting
confidence: 59%
“…This was attributed to the fact that once there is enough HLS to complex iron further addition of this substance only results in an inner filter effect or quenching of the reactive species by the excess of HLS. In fact, EPR measurements in the Fenton process in the presence of CVT230 showed a decrease in the signal attributed to ·OH in the presence of high amounts of this substance . Finally, addition of extra amounts of hydrogen peroxide is sometimes required, which might make the process unattractive under some experimental conditions …”
Section: Hlss In Homogeneous Systems: Photocatalysts and Auxiliaries ...mentioning
confidence: 99%
“…In fact, EPR measurements in the Fenton process in the presence of CVT230 showed a decrease in the signal attributed to •OH in the presence of high amounts of this substance. 35 Finally, addition of extra amounts of hydrogen peroxide is sometimes required, which might make the process unattractive under some experimental conditions. 25 A potentially interesting application of the HLS-driven photo-Fenton reaction is the treatment of scarcely soluble pollutants.…”
Section: Photocatalysts and Auxiliaries For The Photo-fenton Processmentioning
confidence: 99%
“…By comparison with previous studies, similar trends have been observed when Humiclike Substances (HLS) are used as auxiliaries of the photo-Fenton reaction (Table 1). For instance, García-Ballesteros et al 2018 [18] and García-Negueroles et al 2019 [17] concluded that the degradation of caffeine (in a photo-Fenton system at pH = 5) was increased by the addition of different HLS in the range of 10-60 mg•L −1 . Moreover, Gomis et al 2014 [41], tested soluble bio-based substances (with the presence of phenolic carbon, phenoxy and carboxylic functional groups), obtaining an enhancement of the photo-Fenton reaction at pH 5.2.…”
Section: Effect Of Catechol In Photo-fenton and Persulfate-based Systemsmentioning
confidence: 99%
“…Another interesting source of iron ligands are humic-like substances, which have been shown to be efficient for the enhancement of photo-Fenton processes (Table 1) [17][18][19]. Interestingly, a recent study suggests that iron chelated by humic substances is the major reservoir of Fe-complexed in oceans [20].…”
Section: Introductionmentioning
confidence: 99%